Proceedings of the 2001 IEEE Computer Society Conference on Computer Vision and Pattern Recognition. CVPR 2001
DOI: 10.1109/cvpr.2001.990992
|View full text |Cite
|
Sign up to set email alerts
|

Issues on the geometry of central catadioptric image formation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
110
0

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 9 publications
0
110
0
Order By: Relevance
“…Based on their unified model (see Section 3.1.5), they showed that from two respectively three images of lines, one may fully calibrate a central hyper-catadioptric respectively para-catadioptric camera. They gave an algorithm for the para-catadioptric case; Barreto and Araújo developed an algorithm for hyper-catadioptric cameras [28,31] as well as an improved algorithm for para-catadioptric ones that is able to fully compute the mirror shape [30,32]. Ying and Hu, Vandeportaele et al, and Wu et al gave similar algorithms [518,537,551].…”
Section: Lines -The Plumb-line Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their unified model (see Section 3.1.5), they showed that from two respectively three images of lines, one may fully calibrate a central hyper-catadioptric respectively para-catadioptric camera. They gave an algorithm for the para-catadioptric case; Barreto and Araújo developed an algorithm for hyper-catadioptric cameras [28,31] as well as an improved algorithm for para-catadioptric ones that is able to fully compute the mirror shape [30,32]. Ying and Hu, Vandeportaele et al, and Wu et al gave similar algorithms [518,537,551].…”
Section: Lines -The Plumb-line Approachmentioning
confidence: 99%
“…Barreto and Araújo proposed a modified version of this model and used it to study various geometric properties, especially those related to line images and their application for calibration [25,28,29]. Mei and Rives proposed to extend the model by adding classical terms for radial and tangential distortion [339].…”
Section: Global Camera Models 55mentioning
confidence: 99%
“…According to [9,3], all central catadioptric cameras can be modeled by a unit sphere and a perspective projection, such that the projection of 3D points can be performed in two steps (Fig. 1).…”
Section: Sphere Camera Modelmentioning
confidence: 99%
“…We integrate the sphere camera model [9,3], which describes any central catadioptric system, selecting it by one single parameter, with the partial differential equations on manifolds framework through the heat diffusion equation [5,1]. Using this framework and the mirror parameter we compute the metric representing that particular reflecting surface.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the method proposed can work not only with classical perspective cameras but can also be applied to wide-angle cameras obeying the unified model [9,2]. Wide-angle cameras include catadioptric systems that combine mirrors and conventional cameras to create omnidirectional cameras providing 360 o panoramic views of a scene, or dioptric fish-eye lenses [1,5].…”
Section: Introductionmentioning
confidence: 99%